Pathogenicity Analysis of Weaned Piglets Challenged With Novel Emerging Senecavirus A in Fujian, China - Liu, Cun; Liu, Yanhan; Li, Xiubo; Liang, Lin; Cui, Shangjin (Frontiers in veterinary science, 2021)
In order to evaluate the pathogenicity of Senecavirus A (SVA) to weaned piglets preliminarily, 28-day-old weaned piglets were challenged with SVA by intramuscular injection. The clinical manifestations, antibody levels, and tissue viral load of infected piglets were detected. The results indicated that the piglets challenged with SVA CH/FuJ/2017 showed drowsiness, lameness, oral blisters, diarrhea, and other clinical signs. Lesions on the hooves were observed. Red spots or plaques were initially observed on the hoof and then developed into blisters that cracked and gradually formed scab. The symptoms and signs were relieved after 8 days post-infection (dpi). The sentinel piglet, feeding together with the challenged piglets, showed similar clinical signs with the challenged piglets after 3 dpi. Monitoring of antibody levels showed that anti-SVA antibody could be detected at 5 dpi by competition enzyme-linked immunosorbent assay (cELISA) method, and neutralizing antibody could be detected after 7 dpi. Analysis of viral tissue distribution and viral load indicated that SVA could replicate in the liver, spleen, lung, kidney, and lymph node. In all, Senecavirus disease was successfully replicated by SVA CH/FuJ/2017 isolate, which verified the clinical manifestations of SVA infection in weaned piglets, and provided a foundation for further SVA pathogenesis and vaccine development.